Automatic detection of small bowel contraction frequencies in motility plots using lomb‐scargle periodogram and sinus‐fitting method—initial experience. Issue 2 (6th March 2013) - Bickelhaupt, Sebastian; Cattin, Roger; Froehlich, Johannes M.; Raible, Stephan; Bouquet, Hanspeter; Bill, Urs; Patak, Michael A.
<x xml:space="preserve">Abstract</x> Purpose Contraction frequencies are an important parameter for the analysis of bowel motility in MRI. The contraction curve can be rather noisy and the frequency‐evaluation might be difficult. The aim was to evaluate manual calculations of small bowel contraction frequency in comparison with automatic calculations using two mathematically established methods. Methods The institutional‐review‐board approved study consisted of 48 segmental small‐bowel motility‐plots out of a previous study with 25 patients (15 men/10 women; mean 39 years, standard deviation ± 14.67) undergoing MRI (1.5 T, GE‐Medical Systems; two‐dimensional‐Fiesta, pulse repetition time 2.91, echo time 1.25, flip‐angle 45°, matrix 256 × 256, slice thickness 10 mm) were evaluated. Calculations of contraction frequency was performed either manually or using Lomb‐Scargle‐periodograms and Sinus‐Fitting method. The results were compared using intraclass correlation coefficient, Friedman's‐test and Wilcoxon‐matched‐paired‐signed‐rank‐test (P < 0.05 considered statistically significant). Results Mean contraction frequency was 5.69 (standard deviation ± 1.99) for manual calculations showing moderate interreader reliability (intraclass correlation coefficient 0.72; 95% confidence‐interval: 0.59;0.82). No significant difference (P = 0.776) was found to Lomb‐Scargle‐periodograms (5.34 contractions‐per‐minute [cpm], standard deviation ± 2.47; P = 0.174) and to the sinus‐fitting‐method (5.47 cpm; standard deviation ± 2.57; P = 0.0779). For the latter calculations failed in 3/48 plots, while manual and Lomb‐Scargle‐periodograms could be performed successfully in all 48/48 plots. Conclusion Herein, we could show that Lomb‐Scargle‐periodograms and Sinus‐Fitting are fast and reliable methods to automatically measure small‐bowel contraction frequencies even in noisy small bowel motility plots. Magn Reson Med 71:628–634, 2014. © 2013 Wiley Periodicals, Inc.